First description of the tadpole of Theloderma ryabovi Orlov, Dutta, Ghate et Kent, 2006 (Anura: Rhacophoridae), an endemic mossy frog from Vietnam - Kropachev, Ivan I.; Orlov, Nikolai L.; Ostroshabov, Alexander A.; Nguyen, Tao Thien (Zootaxa, 2019)
To date, 26 species of Theloderma have been described and all are distributed throughout Southeast Asia from Assam in northeastern India to Myanmar, Indochina, the Malay Peninsula, and the islands of the Greater Sundas: Sumatra and Borneo (Frost 2019). The tadpoles of only 12 species have been described and published: T. asperum (Boulenger); T. auratum Poyarkov, Kropachev, Gogoleva & Orlov; T. bicolor (Bourret); T. corticale (Boulenger); T. gordoni Taylor; T. horridum (Boulenger); T. leave (Smith); T. moloch (Annandale); T. nebulosum Rowley, Le, Hoang, Dau & Cao; T. palliatum Rowley, Le, Hoang, Dau & Cao; T. stellatum Taylor; T. vietnamense Poyarkov, Orlov, Moiseeva, Pawangkhanant, Ruangsuwan, Vassilieva, Galoyan, Nguyen & Gogoleva (Boulenger 1903; Annandale 1912; Wassersug et al. 1981; Inger et al. 1999; Leong & Lim 2003; Inthara et al. 2005; Rowley et al. 2011; Gawor et al. 2012; Orlov et al. 2012; Poyarkov et al. 2015; Kropachev et al. 2018).